Status of skate populations in the Barents Sea in the recent warm period - Dolgov, Andrey V. (Journal of ichthyology)
Based on ecosystem survey data in the Barents Sea in August-October 2004-2021. the results of studies of the distribution and size-sex composition of seven species of skates (Amblyraja radiata, Amblyraja hyperborea, Rajella fyllae and Bathyraja spinicauda as well as Dipturus oxyrinchus, Leucoraja fullonica and Rajella lintea), as well as estimates of the abundance and biomass of four common skate species. An expansion of the area and the northern and/or eastern boundaries of the distribution of warm-water boreal species of skates (round, spinytail) and some increase in their abundance and biomass were revealed. At the same time, a decrease in the abundance and biomass of the Arctic skate and a shift in its distribution to the cold-water part of the Barents Sea were noted. Significant changes in the size and sex composition of the majority of skate species were not revealed.